Mechanistic understanding of salt-induced drug encapsulation in nanosuspension via acid-base neutralization as a nanonization platform technology to enhance dissolution rate of pH-dependent poorly water-soluble drugs - Van Ngo, Hai; Park, Chulhun; Tran, Thao T.D.; Nguyen, Van Hong; Lee, Beom Jin (European Journal of Pharmaceutics and Biopharmaceutics, 2020)
An acid-base neutralization technique has generated interest for the ability to achieve an enhanced dissolution of pH-dependent weakly basic or acidic poorly water-soluble drugs. However, the underlying nanonization mechanism, following acid-base neutralization, requires further elucidation. We hypothesized that the nanosuspensions (NSPs) via nanonization of drug particles could be attributed to the “salt-induced effect” and surfactant-driven micellization after acid-base neutralization. Rebamipide (RBM) and valsartan (VAL) were chosen as model drugs owing to poor water solubility and pH-dependent aqueous solubility. The drug NSP was rapidly obtained via salt formation (NaCl) after neutralization of the drug in basic NaOH solution and poloxamer 407 (POX 407) in acidic HCl solution. The NSP surrounded by NaCl salt was further stabilized by POX 407. The resulting NaCl salt modulated the critical micelle aggregation of POX 407, stabilizing the drug-loaded NSP in a cage of salt and micellar surfactant. In non-assisted homogenization, size analysis indicated the relationship between salt concentration and size reduction. Fourier transform infrared (FTIR) spectra revealed that the existence of hydrogen bonding between the drug and surfactant after neutralization, attributed to NSP size reduction. Changes in drug crystallinity to the nano-amorphous state were confirmed by powder X-ray diffraction (PXRD). Overall, the salt-induced drug NSP synergistically enhanced the dissolution rate, narrowing a gap between drug dissolution profiles in different pH environments.
Keywords: Chemistry, Pharmaceutical; Drug Liberation; Hydrogen-Ion Concentration; Nanoparticles; Nanotechnology; Particle Size; Poloxamer; Sodium Chloride; Solubility; Spectroscopy, Fourier Transform Infrared; Suspensions; Water; X-Ray Diffraction; Acid-base neutralization; Crystallinity index; Enhanced dissolution; Hydrogen bonding; Nanosuspension; pH-dependent drugs; Salt-induced effect; Surfactant-driven nanonization